1999
DOI: 10.1111/j.1532-5415.1999.tb01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shoe Collar Height and Sole Hardness on Balance in Older Women

Abstract: The findings indicate that subjects had better balance when wearing shoes with high collars than when wearing shoes with low collars and that sole hardness was not related to balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 12 publications
1
58
1
2
Order By: Relevance
“…Two of the 18 selected papers were excluded because no inclusion or exclusion criteria were described [35,36]. Two Cohort studies and low quality RCTs 3a Systematic reviews of case control studies 3b…”
Section: Resultsmentioning
confidence: 99%
“…Two of the 18 selected papers were excluded because no inclusion or exclusion criteria were described [35,36]. Two Cohort studies and low quality RCTs 3a Systematic reviews of case control studies 3b…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of studies analyzing the effects of footwear on the COP excursion are inconsistent. Some studies report differences in quiet stance COP excursions between barefoot and shod standing (Brenton-Rule et al 2011) or between different types of footwear (Lord et al 1999), while several other studies found no significant difference between barefoot and shod conditions Bashford 1996, Landry et al 2010) or between different types of footwear (Lindemann et al 2003, Whitney and Wrisley 2004, Van Geffen et al 2007, Wilson et al 2008, Brenton-Rule et al 2011. Only for "extreme" cases of footwear, quiet stance experiments have been able to conclusively document an effect on the postural control system, for instance, for high heeled shoes (Menant et al 2008) or for so called "unstable" shoes, such as the MBT TM shoe (Masai Barefoot Technology Inc., Switzerland) which creates increased instability through a rocker sole and a soft heel pad (Nigg et al 2006a.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no consensus as to which sole material best prevents slipping. Experiments conducted by different researches have shown that during slip tests polyurethane soles undergo considerable wear and Footwear with high collars is preferable over footwear with low collars from the point of view of balance in persons 60 years of age and older [27]. A stable human heel position within footwear is another critical factor preventing slips [31].…”
Section: Vitmentioning
confidence: 99%